Prose and Poetry in Eugenio Montale’s lyrical poetry. - Rodríguez Fierro, Mercedes (Cuadernos de Filología Italiana, 2004)
Italian twentieth century poetry clearly shows the blurring of the borders between prose and poem. This genre indefinition reveals itself in the majority of authors and poetical trends, reflecting the inclination to open the poetical discourse to new linguistic and formal registers, as well as to new contents, thus getting nearer to the dialects context. Critics have pointed the existence of this tendency in Eugenio Montale. The combination of poetry and prose can be detected not only in his late writings, but also in some texts of his early production.